Effect of customized healing abutments on the peri‐implant linear and volumetric tissue changes at maxillary immediate implant sites: A 1‐year prospective randomized clinical trial. (22nd August 2021) - Fernandes, Danilo; Nunes, Sílvia; López‐Castro, Gonzalo; Marques, Tiago; Montero, Javier; Borges, Tiago
Abstract: Background: Immediate implant placement (IIP) associated with the use of bone substitutes and collagen matrices (CM) seems to reduce the amount of resorption at peri‐implant areas. Recently, customized healing abutments (CA) appeared as another solution in order to seal the socket and preserve the original soft tissue contour. Purpose: To evaluate peri‐implant tissues dimensional changes after using customized healing abutments compared with the use of xenogeneic collagen matrices as socket sealing options in flapless maxillary immediate implant placement. Material and methods: The present study was designed as a prospective, randomized, controlled clinical trial. Patients were allocated into two groups depending on the socket sealing option: in the CM group a collagen matrix was used and in the CA group a customized abutment. Digital impressions were taken prior to extraction, 1, 4, and 12 months after implant insertion and the digital files allowed to evaluate linear buccal changes (MBC) and the buccal volumetric variation (BVv) between the different time points at peri‐implant tissue areas. Additionally, mucosa variation was computed assessing the papilla presence and the midfacial mucosa height. Statistical significance was set at 0.05. Results: Twenty‐eight patients were observed during a 12‐month period. Significant differences between mean values of BVv at the first month were observed at the CM and CA group (−9.75 ± 6.65% and −4.76 ± 5.29%, respectively) ( p  = 0.043). At the 1‐year follow‐up, no significant differences were found in terms of BVv between the two groups, although the thin bone phenotype (≤1 mm) significantly influenced the volumetric variations that occurred in each group. No significant differences were noticed in midfacial mucosa and papillae alteration between groups, after 1 year of treatment. Conclusion: Both treatment options are predictable solutions for socket sealing in IIP, although a higher volumetric variation can be expected in the presence of thin bone phenotypes.